The effectiveness of the offender personality disorder pathway: a propensity score-matched analysis - Vamvakas, George (Psychology, crime & law, 2025)
Offenders with severe personality pathology are at significantly increased risk of serious and violent offending. In England and Wales, offenders who are likely to meet criteria for a diagnosis of personality disorder are managed within a network of ‘Offender Personality Disorder Pathway’ services. We conducted a retrospective cohort study over 6 years, using linked routine datasets, to examine the effectiveness of these services on male offenders (n = 28,321). We compared the outcomes of those who received a simple case formulation and had not been referred to Pathway services (the ‘Comparison group’), with a group of offenders who had received a complex case formulation and been referred to Pathway services (the ‘Treatment group’). Over time, significant improvements occurred in re-offending risk scores, and lower rates of behavioural disturbance among both Treatment and Comparison groups of offenders. However, no statistically significant differences were detected in the rates of improvement between Treatment and Comparison groups. Offending rates in both groups significantly increased over time, although there was no significant difference in the increase in offending rates between the Treatment and Comparison groups. Currently, there is no statistical evidence that the Pathway is associated with changes in offender behaviour.